Study and diachronic analysis of forest cover changes of Belezma-Algeria. - Barbache, Amina; Beghami, Yassine; Benmessaoud, Hassen (Geographica Pannonica, 2018)
This study aims to analyze the changes in forest cover in the forest of Belezma-BATNA, during a period of 31 years (1986 to 2017), based on the use of remote sensing data (diachronic analysis of satellite images Landsat) by calculating indices (NDVI et NDWI). The results revealed significant changes during this period; Regressive changes in vegetation cover, particularly between 2000 and 2017. This degradation is mainly located in the southern and southeastern part of the Belezma forest resulting from several natural and anthropogenic factors. It can be considered that drought is one of the main causes causing the regressive change of the forest during this period with other factors that promote this degradation such as overgrazing, fire, phytosanitary problems (caterpillar processionary), etc.
Keywords: remote sensing; change detection; analysis of forest; forest cover; diachronic analysis